Gut Microbiome Alterations in Patients With Carotid Atherosclerosis - Chen, Jingfeng; Qin, Qian; Yan, Su; Yang, Yang; Yan, Hang; Li, Tiantian; Wang, Lin; Gao, Xinxin; Li, Ang; Ding, Suying (Frontiers in Cardiovascular Medicine, 2021)
Carotid atherosclerosis (CAS) is a reflection of systemic atherosclerosis and the main pathological processes of cardiovascular disease (CVD), namely, carotid intima–media thickening, carotid plaque formation, and carotid stenosis. Accumulating evidence indicates that the gut microbiota plays an important role in CVD and gut–brain disorders, but the associations of the composition and metabolites of the gut microbiome with CAS have not been studied comprehensively. We performed a gut microbiome genome-wide association study in 31 patients with CAS and 51 healthy controls using whole-genome shotgun sequencing. We found that several risk factors (waist circumference, body mass index, diastolic blood pressure, systolic blood pressure, fasting blood glucose, glycated hemoglobin A1c, total cholesterol, triglyceride, and low-density lipoprotein cholesterol) and inflammatory markers (white blood cell count and absolute value of neutrophils) were significantly higher in the CAS group than in the control group. In addition, 21 species and 142 pathways were enriched in the CAS group, and 10 species and 1 pathway were enriched in the control group. Specifically, Bacteroides eggerthii, Escherichia coli, and Klebsiella pneumoniae were the most abundant species in the CAS group, whereas Parabacteroides unclassified, Prevotella copri, Bacteroides sp 3_1_19, and Haemophilus parainfluenzae were the most abundant species in the control group. Finally, we found that most gut microbes and microbial pathways that were enriched in the CAS group had significant positive correlations with clinical characteristics, whereas the microbes and pathways enriched in healthy controls had significant negative correlations with clinical characteristics excluding high-density lipoprotein cholesterol. In addition, the associations between gut microbes and some microbial pathways (short-chain fatty acid, lipopolysaccharide, and menaquinol biosynthesis) were identified. Our results indicate the existence of a cyclic pathway that elevates the circulating concentrations of trimethylamine-N-oxide in patients with CAS but reduces its concentrations in healthy controls.